2021
DOI: 10.1016/j.heliyon.2021.e06225
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of adenovirus strains represented species B and E isolated from broiler chicken flocks in eastern Poland

Abstract: Fowl adenovirus strains were isolated from the internal organs of 3-wk-old broiler flocks exhibited clinical signs associated with inclusion body hepatitis (IBH). The isolated strains were molecularly characterised and sequencing revealed three distinct clusters. One cluster showed close proximity at the nucleotide level with adenovirus type/species - 6/E, 7/E, 8a/E, and 8b/E. The second cluster contained five reference sequences belonging to the species FAdV-D and E. A third cluster contained one field and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…In addition, several reports of IBH and/or HHS were documented in Japan ( 31 ), Korea ( 32 ), India ( 33 ), Pakistan ( 34 ), Spain ( 25 ), Poland ( 35 ), Iran ( 36 ), Mexico ( 37 ), Brazil ( 38 ), Croatia ( 39 ), Australia ( 40 ), Greece ( 41 ), Iraq ( 42 ), Palastine ( 43 ), United Arab Emirates ( 44 ), Saudi Arabia ( 45 ), Morocco ( 46 ), and South Africa ( 47 ).…”
Section: Current Status Of Ibh And/or Hhs Associated Problemsmentioning
confidence: 99%
“…In addition, several reports of IBH and/or HHS were documented in Japan ( 31 ), Korea ( 32 ), India ( 33 ), Pakistan ( 34 ), Spain ( 25 ), Poland ( 35 ), Iran ( 36 ), Mexico ( 37 ), Brazil ( 38 ), Croatia ( 39 ), Australia ( 40 ), Greece ( 41 ), Iraq ( 42 ), Palastine ( 43 ), United Arab Emirates ( 44 ), Saudi Arabia ( 45 ), Morocco ( 46 ), and South Africa ( 47 ).…”
Section: Current Status Of Ibh And/or Hhs Associated Problemsmentioning
confidence: 99%
“…FAdVs are commonly present in fowl farms worldwide [17]. As reported, more and more FAdVs have been isolated from dead or sick animals in recent years [2,6,[18][19][20]. FAdV infections are associated with a range of avian infectious diseases, such as IBH and HHS.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, genotype FAdV-8a/E2 has also been isolated sporadically in AGE outbreaks [ 40 ]. In contrast, genotype FAdV-6/E1 was genotyped in IBH outbreaks [ 41 ] and genotype FAdV-11/D3 has also been identified in birds with RSS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the birds analyzed in this study were not vaccinated, so it can be deduced that the viral strains that are present in commercial batches are field strains. Many studies showed that the genotypes characterized here were associated with outbreaks of IBH or HHS in chickens in several countries around the world [ 41 , 46 , 47 , 48 ]; however, the vast majority of reports of IBH or HHS worldwide have been associated with FAdV-4/C1 [ 23 , 49 , 50 , 51 , 52 ] and the report of a large number of outbreaks associated with this FAdV genotype has led many studies to focus on the development of vaccines based on this viral genotype [ 53 , 54 , 55 ], as well as associations with other genotypes (FAdV-8b/E3) where excellent protection against infections with both genotypes is shown [ 1 , 12 , 56 , 57 , 58 ]. However, these recombinant vaccines have not been tested with other FAdV genotypes that are included in the same group to which the vaccine strains belong, in the case of FAdV-8b/E3 belonging to species E, perhaps it could generate protection against FAdV-8a/E2 and FAdV-6/E1 strains and be an alternative in the country.…”
Section: Discussionmentioning
confidence: 99%